Compromised GCF total antioxidant capacity in periodontitis: cause or effect? - I. L. C. Chapple (Blackwell Synergy, 2007)
Background: Oxidative stress is implicated in the pathogenesis of periodontitis. The total antioxidant capacity (TAOC) of gingival crevicular fluid volume (GCF) and plasma appears compromised in periodontitis, but it is unclear whether this predisposes to, or results from the inflammatory process. Aim: To investigate longitudinal changes in GCF and plasma TAOC following reductions in periodontal inflammation with successful non-surgical therapy. Materials and Methods: Two longitudinal studies were run in series on non-smokers with chronic periodontitis (CP). Study-1 (n517) assessed index sites with mild disease; Study-2 (n518) investigated deep sites. GCF sampling and clinical measures were performed at baseline and 3 months post-therapy. Plasma and GCF TAOC was determined by enhanced chemiluminescence and 32 age/sex-matched periodontally healthy controls were used.